La politica autarchica e la comunità chimica italiana: Il ruolo di Nicola Parravano - Calascibetta, Franco (Chimica nella Scuola, 2022)
The adhesion of the Italian chemical community to fascism was, as is well known, quite generalized, apart from some personal exceptions. The consensus that personalities from the academic and industrial world showed towards the regime was particularly convinced in the years in which the autarkic policy was born and developed. This contribution aims to describe in particular the position of complete consonance with the scientific programs of fascism of Nicola Parravano, who was one of the most important leaders of the Italian chemical community in the years between the two world wars.